Conception of Monetary Policy Institutional Structure Reforming in the Republic of Belarus - Золотарева (O.A. Zolotareva), О.А.; Хмель (O. Khmel), О.А. (Экономика и банки, 2017)
It is shown in the paper that under current institutional conditions in the Republic of Belarus necessary for the real economy stimulating economic policy turns to be impossible. The main reason for such situation is the underdevelopment of the financial market adsorbing excess liquidity. It is also shown that in the countries with special dominance of the banking segment in the structure of financial system it is almost impossible to create a solid basis for long–term investing. At the same time, legal conditions for capital market and business development exist in the Republic of Belarus. The main obstacle in the development of the privatization processes considered by the author is the crisis of vertical and horizontal trust, which manifests itself in the well–known in the economic theory paradox of voting while making investment decisions. The creation of a new macro–economic structure – the Investment Bank of the first tier with the original scheme of attraction and placement of funds, which will allow to overcome the paradox of voting while making investment decisions and, therefore, will initiate the development of large–scale circulation of capital assets in the Republic of Belarus was suggested in the paper. Key words: financial market, monetary policy, financial depth, voting paradox, privatization, investment, Investment Bank of the first tier, innovative clusters.